Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Áp dụng tính chất của dãy tỉ số bằng nhau ta có:
( 2x+1)/5 = (3y-2)/7 = (2x+3y-1)/ 6x = (2x+1+3y-2)/ 5+7 = (2x+3y-1)/ 12 = (2x+3y-1)/ 6x
Th1: Nếu 2x+3y-1 = 0 => (2x+1)/ 5 = (3y-2)/ 7 = 0
=> | 2x+1=0 => | x= -1/2
| 3y-2=0 | y= 2/3
![](https://rs.olm.vn/images/avt/0.png?1311)
1,
\(\frac{25}{12}+\left(\frac{-4}{12}\right)=\frac{7}{4}\)
\(\frac{-10}{8}+\frac{15}{4}=\frac{5}{2}\)
\(\frac{3}{8}+\frac{-14}{6}=\frac{-47}{24}\)
\(\frac{350}{150}+\left(\frac{-200}{360}\right)=\frac{16}{9}\)
\([\frac{5}{8}+\left(\frac{-3}{4}\right)]+\frac{15}{6}=\frac{-1}{8}+\frac{15}{6}=\frac{19}{8}\)
\(\frac{7}{3}+[\left(\frac{-5}{6}\right)+\left(\frac{-2}{3}\right)]=\frac{7}{3}+\left(\frac{-3}{2}\right)=\frac{5}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
=3x\(^4\)+(\(-\dfrac{3}{4}x^3+\dfrac{1}{5}x^3\))+2x\(^2\)+(8x-9x)+(\(-3+\dfrac{2}{5}\))
=\(3x^4-\dfrac{11}{20}x^3+2x^2-x-\dfrac{13}{15}\)
B(x)-A(x)=